Factors affecting treatment success in individuals applying to a smoking cessation outpatient clinic - Kocakaya, Derya; Şenol, Hatice; Aslan, Sezer; Çırakoğlu, Ahmed Mahmud; Çakır Fidan, Merve Nur; Telci, Hatice; Çetinkaya, Mehmet Zahid; Yıldızeli , Şehnaz Olgun; Özaydın, Ayşe Nilüfer; Ceyhan, Berrin (Journal of Dependence, 2022)
Objective: Nicotine addiction causes continuity of smoking and unsuccessful cessation attempts. Many factors affect nicotine addiction. This study aims to determine which factors are more effective in the smoking cessation success of smokers, aged 18 and over. Method: This research is planned as retrospective cohort design. The patients applied to our outpatient called by phone. After getting oral permission, they were asked the questionnaire. Results: 190 participants of survey answered the phone (79%); 32.1% of them was female (n=61) and 67,9% of them was male (n=129). Median age of participants was 39.5 (Interquartile Range:19, min:19 max:78). Smoking success was detected in 32.6% of males (n=42) and 14,8% of females (n=9). Patients older than 50 years were able to stop smoking better than the patients younger than 50 years old. Early smokers were (first smoking before 15 years old) statistically worse for smoking cessation than late smokers. Smoking cessation success is 3.86-fold higher than females. Being a late smoker increases the cessation success 5.33f-old compared to early smokers and regular service visits increase the smoking cessation success by 4.31-fold compared to non-regular participants. Conclusion: Smoking cessation success, which was higher in men, increased significantly in those who started smoking at a later age and who continued their treatment regularly. In our county, where there is still a high rate of cigarette consumption, it is important to ensure the continuity of smoking cessation outpatient clinics, which are important structures to reduce cigarette addiction.